AQ-12 Application of a Multiplex PCR Assay to Detect Campylobacter fetus subspecies venerealis from Imported Bovine Preputial Samples - Mazdani Daulay; Adi Komara; Novera Nirmalasanti; Siti Khadijah; . Marjono; Melyna Sandra; Muhamad Taopik; . Mukromin; . Mustamil; Rahmat Setya Adji (Hemera Zoa, 2018)
Campylobacteriosis, caused by Campylobacter spp., is of considerable economic importance to the cattle industry worldwide. Campylobacter spp. were recognized as etiological agents of abortion in sheep. Campylobacter fetus subsp. fetus (Cff) causes sporadic abortion in sheep, often late in gestation, while subspecies venerealis (Cfv) is a cause of sexually transmitted bovine infertility and sporadic abortion in cattle. Various investigations have been carried out in different countries to assess the prevalence and impact of this disease. Some published results surveys are outlined in Table 1. Table 1. A summary of published data showing the prevalence of C. fetus in different countriesStudyareaSample type(s)Sample sizePrevale nce ofC. fetus (%)Diagnostic methodAustralia(1985-1986) Bulls (preputi al suction)1 008animals41 herds87% herdspositiveSerological(Fluorescentantibody test) California(United States of America)Cows40047Serological(ELISA) New ZealandCows (vaginal mucous) and bulls (preputial wash)1 230 cows(125 herds)54 bulls70% herds positiveCfv : 0Cff/othersSerological(ELISA)Bacteriological culture          Cff: Campylobacter fetus subsp. fetus, Cfv: C. fetus subsp. venerealis. According to [1], Bovine Genital Campylobacteriosis (BGC) disease was classified as 1st Group of animal quarantine disease. It is an exotic disease that was not ever detected in Indonesia. However, large scale cattle importation to Indonesia from the countries which ever reported BGC prevalence in their territories, initiating and spreading BGC will be the major threat for feedlotter or dairy farm in Indonesia. Hence, we should apply diagnostic test to detect Cfv in order to prevent the introducing the BGC to Indonesia. The aim of this study was to verify that multiplex PCR assay applicative to detect Campylobacter fetus subsp. venerealis from field samples.